BUILDING DATA WAREHOUSE FOR EMPLOYEE TRAINING MINISTRY OF LAW AND HUMAN RIGHTS - Nugroho, Ari Fauzi Mukti; Kartadie, Rikie; Handayani, Latifah Nurrohmah; Isnaeni, Nenen; kholik, Moh. Abdul (LPPM UTDI (d.h STMIK AKAKOM) Yogyakarta, 2024)
In order to improve and expand each employee's competency and knowledge, education and training are crucial for the Ministry of Law and Human Rights. They may also be utilized for employee mapping. In the past, it was necessary to gather data on things like the number of employees who attended a particular training, which training had reached its participant quota, and the number of graduates in each training. This required extensive processing and repeated cross-checking of data sources to make sure the data was accurate and legitimate before it could be compiled into a table for analysis. Information technology may be used to immediately process employee competence data and education and training results into information. Therefore, it is expected that the Nine Step method, which is part of the Kimball & Ross (2010), methodology will simplify and accelerate the process of processing training data into information presented for analysis and reporting purposes at the leadership level in each work unit. Keywords: data warehouse, OLAP, ETL, pentaho, kemenkumham, training